Disaster on the Spanish Main : The Tragic British-American Expedition to the West Indies during the War of Jenkins' Ear - Chapman, Craig S. (Book collections on Project MUSE., 2021)
"Disaster on the Spanish Main: The Tragic British-American Expedition to the West Indies during the War of Jenkins' Ear presents a thoroughly researched and factual account of the West Indies expedition from its roots in the commercial-imperial conflicts between Britain and Spain to its eventual unraveling in death and despair"--